2015
DOI: 10.1177/1934578x1501000134
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antifungal Activity of Aaronsohnia pubescens Essential Oil from Algeria

Abstract: In the present study, the chemical composition of the essential oil obtained from the aerial parts of Aaronsohnia pubescens (Desf.) K.Bremer & Humphries (Asteraceae), a chamomile-like medicinal plant, was studied. Using both GC-MS and GC-FID methods, 58 volatile compounds could be identified representing 96.6% of the total essential oil composition. The main compounds in the essential oil were monoterpene hydrocarbons such as (Z)-β-ocimene (53.8%), myrcene (15.2%) and α-pinene (7.7%). Moreover, the essential o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…The essential oil of the Biskra populations were composed of spathulenol, elemicine, and herniarine (Bouzaine 2015). On the other hand, the populations of Bechar (Makhloufi et al 2014) showed a similarity in the chemical composition with that of populations in this study.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The essential oil of the Biskra populations were composed of spathulenol, elemicine, and herniarine (Bouzaine 2015). On the other hand, the populations of Bechar (Makhloufi et al 2014) showed a similarity in the chemical composition with that of populations in this study.…”
Section: Discussionsupporting
confidence: 53%
“…Chemical analysis of essential oils of M. pubescens collected from the Ghardaia region shows the presence of ethyl isochrysanthemoate, spathulenol, α-cadinol, and geranyl isovalerate as major components (Boutaghane et al 2011;Tadrent et al 2016). The investigation of the essential oil of M. pubescens collected from the Biskra region showed that the major compounds were spathulenol, elemicine and herniarine (Bouzaine 2015), while study by Makhloufi et al (2014) showed that the essential oil of M. pubescens in the Bechar region is rich in β-ocimene-(Z), myrcene and α-pinene (Table 1). Two species of M. pubescens and M. chamomilla, are morphologically similar, but they differ in essential oils composition (Tadrent et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…called Ouazouaza in arabic, is a medicinal plant that belongs to the Asteraceae family. It is largely distributed in the northern and central Algerian Sahara (Benchelah et al, 2000 andMakhloufi et al, 2015). In Algeria, A. pubescens is widely used in folk medicine as an antiseptic, antirheumatic, antiarthritic, antidiarrheal and to treat digestive complications.…”
Section: Introductionmentioning
confidence: 99%
“…It is also used as a condiment and as an aromata in the preparation of some traditional dishes (Cherif et al, 2017 andHammiche andMaiza, 2006). Several studies of A. pubescens chemical composition revealed its richness in terpenoids (e. g., α-pinine, Z-βocimene α-curcumene and 6-oxo-cyclonerolido), and phenolic compounds such as apigenin, luteolin, quercetin and herniarin (Boutaghane et al, 2011;Makhloufi et al, 2015 andSharifi-Rad et al, 2018). Furthermore, there are no previous reports on the antioxidant and enzyme inhibitory potentials of A. pubescens.…”
Section: Introductionmentioning
confidence: 99%
“…called Ouazouaza in arabic, is a medicinal plant that belongs to the Asteraceae family. It is largely distributed in the northern and central Algerian Sahara (Benchelah et al, 2000 andMakhloufi et al, 2015). In Algeria, A. pubescens is widely used in folk medicine as an antiseptic, antirheumatic, antiarthritic, antidiarrheal and to treat digestive complications.…”
Section: Introductionmentioning
confidence: 99%